2018
DOI: 10.1128/mbio.00067-18
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient and Scalable Precision Genome Editing in Staphylococcus aureus through Conditional Recombineering and CRISPR/Cas9-Mediated Counterselection

Abstract: Staphylococcus aureus is an important human pathogen, but studies of the organism have suffered from the lack of a robust tool set for its genetic and genomic manipulation. Here we report the development of a system for the facile and high-throughput genomic engineering of S. aureus using single-stranded DNA (ssDNA) oligonucleotide recombineering coupled with clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9-mediated counterselection. We identify recombinase EF2132, derived from Enterococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 69 publications
3
75
0
Order By: Relevance
“…We obtained a recombination efficiency of ~5%, similar to that of studies in E. coli (Ellis et al 2001) and higher than previous λ Red Beta and RecT homologous systems found in other bacteria (van Kessel & Hatfull 2007;Yin et al 2015;Yang et al 2015;Swingle, Bao, et al 2010;Oh & Van Pijkeren 2014;Aparicio et al 2018;Penewit et al 2018;Lee et al 2017). In addition, W3 Beta was also functional in E. coli and performed at similar efficiencies to λ Red Beta.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We obtained a recombination efficiency of ~5%, similar to that of studies in E. coli (Ellis et al 2001) and higher than previous λ Red Beta and RecT homologous systems found in other bacteria (van Kessel & Hatfull 2007;Yin et al 2015;Yang et al 2015;Swingle, Bao, et al 2010;Oh & Van Pijkeren 2014;Aparicio et al 2018;Penewit et al 2018;Lee et al 2017). In addition, W3 Beta was also functional in E. coli and performed at similar efficiencies to λ Red Beta.…”
Section: Discussionsupporting
confidence: 85%
“…Adapting recombineering for a new species is challenging; however, because the λ Red and RecET systems do not necessarily maintain high efficiency across different bacteria (Huang et al 2017;Hossain et al 2015;Hu et al 2014), there may be a dependence on host-specific machinery (Datta et al 2008;Muyrers et al 2000). Since recombineering was first applied in E. coli (Datsenko & Wanner 2000;Baba et al 2006), a few other phage homologous recombination systems have been found to promote recombination in Pseudomonas, Vibrio, Lactobacillus, Mycobacteria, Photorhabdus and Staphylococcus (van Kessel & Hatfull 2007;Yin et al 2015;Yang et al 2015;Swingle, Bao, et al 2010;Oh & Van Pijkeren 2014;Aparicio et al 2018;Penewit et al 2018;Lee et al 2017;Datta et al 2008), and we have explored whether this technology can be established in Shewanella. To maximize the recombination efficiency, we identified λ Red recombinase homologs in Shewanella species and have tested a system from Shewanella sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the majority of mutations arising during in-host evolution in S. aureus inactivate protein function (34). To assess genes identified by our selection, we therefore initially generated isogenic single-gene nonpolar deletions using recombineering and CRISPR (clustered regularly interspaced short palindromic repeat)/Cas9-mediated counterselection (63) or obtained bursa aurealis transposon mutants constructed in a different strain background (JE2) (64) when this strategy was unsuccessful. Two genes (mnhA and tufA) could not be constructed as nonpolar deletions, but strains were engineered to carry the specific missense mutations resulting from selection.…”
Section: Resultsmentioning
confidence: 99%
“…A new paper by Guggisberg et al (7) now expands the observations of deer malaria in the United States by providing evidence for a high prevalence of these parasites in farmed white-tailed deer in Florida. The authors followed 33 fawns through their first year of life and observed that over 20% of them acquired infections of the hemosporidians.…”
Section: Commentarymentioning
confidence: 96%